Analysis Of The Value Of Sintren Dance Tourist Attractions As A Tourist Attraction In Cirebon City - Wachyudi, Sudiana; Shabrina, Fitriatunnisa (Jurnal Toursci, 2025)
Background. Cirebon, as one of the cultural heritage centers in West Java Province, boasts various attractions, including natural, religious, social, culinary, and especially dance-related sites. Sintren dance is a traditional culture that has evolved significantly in the northern coastal area of Java. One of the regions that has this Sintren dance art is Cirebon. Purpose. The purpose of this study is to find out the value of tourist attractions contained in the Sintren dance to the public, especially the younger generation, about the legendary story behind the art of Sintren, in order to attract interest in getting to know this typical Cirebon dance. Method. This research activity is a field study, employing a qualitative research method. The data source is based on the results of observations, interviews, and documentation on the value of tourist attractions contained in the Sintren dance. Result. Many art studios are making efforts to preserve this art by carrying out activities and introducing the Sintren dance through performances on stage. However, the existence of Sintren art is almost forgotten due to the lack of interest among residents in learning this art. Conclusion. With this research, it is hoped that the public's interest in legends and traditional arts will increase, and they will become more interested in preserving traditional culture in Indonesia, especially the art of Sintren in Cirebon